Caraval: Finale - Book 3 - Garber, Stephanie (New York Flatiron Books, 2019)
"With lives, empires, and hearts hanging in the balance, Tella must decide if she's going to trust Legend or a former enemy. After uncovering a secret that upends her life, Scarlett will need to do the impossible. And Legend has a choice to make that will forever change and define him"--
Keywords: Sisters -- Juvenile fiction; Performing arts -- Juvenile fiction; Games -- Juvenile fiction; Magic -- Juvenile fiction; Sisters -- Fiction; Performing arts -- Fiction; Games -- Fiction; Magic -- Fiction; Fantasy; Fantasy fiction